Effects on Gambling Activity From Coronavirus Disease 2019—An Analysis of Revenue-Based Taxation of Online- and Land-Based Gambling Operators During the Pandemic - Håkansson, Anders (Frontiers in Psychiatry, 2020)
Background Concerns have been raised about increased gambling problems during the COVID-19 crisis, particularly in settings with high online gambling and risks of migration from land-based to riskier online-based gambling types. However, few non-self-reported data sources are hitherto available. The present study aimed to assess changes in the online and land-based gambling markets in Sweden during the first months affected by the societal impact of COVID-19. Methods Data were derived from national authority data describing monthly taxations of all licensed Swedish gambling operators, whose monthly tax payments are directly based on gambling revenue. Sub-divisions of the gambling market were followed monthly from before COVID-19 onset in Sweden (mainly February, 2020) through June, 2020, when the sports market was re-started after COVID-19 lock-down. Results Overall revenue-based taxations in the licensed gambling marked decreased markedly from February to March, but stabilized onto an overall modest decrease through June. Commercial online casino/betting, despite some decrease in March, was maintained on a relatively stable level through June. However, within this category, horse betting increased steeply during the pandemic but returned to pre-pandemic levels later during the period. The state-owned operator in betting/online casino decreased markedly throughout the pandemic. Remaining commercial operators, mainly in online casino and online betting, demonstrated no change during the pandemic, and ended on a June level 14 percent above the February level. Throughout the pandemic, the smaller restaurant casinos decreased markedly, while major state-owned casinos also closed entirely. State-owned lotteries and electronic gambling machines decreased markedly but were rapidly normalized to pre-pandemic levels. Conclusions Commercial online gambling operators’ revenues remained stable throughout the pandemic, despite the dramatic lock-down in sports. Thus, chance-based online games may have remained a strong actor in the gambling market despite COVID-19 crisis, in line with previous self-report data. A sudden increase in horse betting during sports lock-down, and its decrease when sports re-opened, confirm the picture of possible COVID-19-related migration between gambling types, indicating a volatility with potential impact on gambling-related public health.